2012
DOI: 10.1136/vr.100588
|View full text |Cite
|
Sign up to set email alerts
|

Composite faecal egg count reduction test to detect resistance to triclabendazole in Fasciola hepatica

Abstract: A faecal egg count reduction test, using composite samples, was developed in order to assess the efficacy of the flukicide, triclabendazole (TCBZ) on commercial sheep farms in England and Wales. First, a comparison between individual counts and composite counts was conducted using sheep on two farms with different levels of infection. Faecal samples were collected from 50 sheep on each farm at the time of TCBZ treatment and 21 days later. The results showed that a composite fluke egg count (CFEC) was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…Analysis of fluke infections in cattle in Queensland showed prevalence ranging from 0.4 to over 50% (Roberts, 1982;Baldock and Arthur, 1985;Molloy and Anderson, 2006). Since the 1980s control of fasciolosis in Australia has relied on the use of Triclabendazole (TCBZ) (Boray et al, 1983) but resistance to this drench, first reported in Victoria (Overend and Bowen, 1995), has now been identified in livestock in south-eastern Australia (Brockwell et al, 2014), the United Kingdom, Europe and South America (Alvarez-Sanchez et al, 2006;Daniel et al, 2012;Gordon et al, 2012;Sargison, 2012;Ortiz et al, 2013;Robles-Pérez et al, 2013). Burdens of drug-resistant flukes of 20-34 were observed in cattle following treatment with TCBZ in Australia (Brockwell et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Analysis of fluke infections in cattle in Queensland showed prevalence ranging from 0.4 to over 50% (Roberts, 1982;Baldock and Arthur, 1985;Molloy and Anderson, 2006). Since the 1980s control of fasciolosis in Australia has relied on the use of Triclabendazole (TCBZ) (Boray et al, 1983) but resistance to this drench, first reported in Victoria (Overend and Bowen, 1995), has now been identified in livestock in south-eastern Australia (Brockwell et al, 2014), the United Kingdom, Europe and South America (Alvarez-Sanchez et al, 2006;Daniel et al, 2012;Gordon et al, 2012;Sargison, 2012;Ortiz et al, 2013;Robles-Pérez et al, 2013). Burdens of drug-resistant flukes of 20-34 were observed in cattle following treatment with TCBZ in Australia (Brockwell et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…However, this heavy reliance on TCBZ to treat sheep and cattle in particular, has resulted in resistance to TCBZ, which was first reported in fluke populations in Australia in 1995 and is now well established in the Netherlands, Ireland, Spain and all UK regions (Fairweather, 2005;Brennan et al 2007). In the UK, our own studies in England and Wales showed that TCBZ resistance was evident on seven out of 25 farms analysed (Daniel et al 2012). The movement of livestock around the country facilitates the spread of TCBZ resistant (TCBZ-R) F. hepatica populations throughout the UK with the potential for considerable economic consequences to livestock production such as that recently reported by Sargison and others Sargison and Scott, 2011).…”
Section: T C B Z R E S I S T a N C Ementioning
confidence: 93%
“…A comprehensive review of methods for detecting resistance falls outside the scope of this article but key considerations in this area involve the ongoing evaluation of methods applicable to the live host such as the faecal egg count reduction tests (FECRT) and coproantigen reduction test (Flanagan et al 2011a, b;Daniel et al 2012). Whilst these approaches are open to interpretation, multiple studies demonstrate TCBZ efficacy in vivo using treatment and necropsy approaches.…”
Section: Detecting Tcbz Resistancementioning
confidence: 98%
“…This is important if tests of flukicide efficacy are to be performed. The liver fluke egg count reduction test has so far been validated only for investigating triclabendazole efficacy (Daniel and others 2012). As with other anthelmintics, a drench test may be performed using pooled faeces, but the interval between treatment and sampling must be a minimum of three weeks given the prolonged and sporadic release of liver fluke eggs from the gall bladder.…”
Section: Trematode Parasitesmentioning
confidence: 99%